Investigation of Scutellaria Barbata’s immunological mechanism against thyroid cancer using network pharmacology and experimental validation - Gen Ouyang; Yuangui Zhu; Zhehao Ouyang (Scientific Reports)
Abstract Thyroid cancer (TC) is the most common endocrine malignancy, with a rapidly increasing global incidence. Scutellariae Barbatae Herba (SBH) exhibits significant antitumor activity; however, its mechanism against TC remains unclear. This study aims to explore the immunotherapeutic mechanism of SBH in treating TC through network pharmacology, bioinformatics analysis, and experimental validation. In the TCMSP database, the active components and potential targets of SBH were screened to construct a drug-component-target-disease network. TC targets were then filtered, and common targets were selected to build a protein-protein interaction network. GO and KEGG enrichment analyses were performed. The expression, prognosis, and immunotherapeutic roles of core genes were validated using TCGA databases. Molecular docking demonstrated the binding interactions between core components and targets. Finally, in vitro experiments were conducted to validate the results of the network pharmacology analysis. 14 active components and 29 potential targets of SBH in treating TC were identified from the TCMSP database. PPI network analysis highlighted SPP1 as a key target. GO enrichment analysis involved 722 biological processes, 24 cellular components, and 73 molecular functions. KEGG enrichment analysis suggested that the anticancer effect of SBH might be mediated through signaling pathways such as AGE-RAGE and PI3K-Akt. TCGA data indicated that SPP1 is highly expressed in TC and is associated with diagnosis, pathological stage, N stage, and gender of TC patients. Additionally, SPP1 expression correlated with the infiltration of 24 types of immune cells, with the highest correlation observed with macrophages. Molecular docking demonstrated that SPP1 has high binding stability with quercetin, Rhamnazin, and Salvigenin, with binding energies of -8.117, -7.494, and − 7.202 kJ∙mol − 1, respectively. Experimental validation showed that quercetin inhibited the growth of TC cells in a dose-dependent manner. Protein results indicated that quercetin downregulated SPP1 mRNA and protein expression. This study combines database predictions with experimental validation to reveal the potential mechanisms of SBH against TC, providing effective strategies for the immunotherapy of TC.